2020
DOI: 10.1155/2020/5419846
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride/High-Density Lipoprotein Cholesterol Ratio Is Associated with In-Hospital Mortality in Acute Type B Aortic Dissection

Abstract: Background. Triglyceride/high-density lipoprotein cholesterol (TG/HDL-c) ratio varies with vascular and other metabolic diseases. However, its role in acute type B aortic dissection is not well understood. In the current study, we evaluated the relationship between TG/HDL-c ratio and in-hospital mortality in type B aortic dissection. Methods. We performed a retrospective analysis of consecutive patients between January 2015 and December 2018, by targeting dependent (TG/HDL-c ratio) and independent (inhospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…(34) In addition, high serum HDL-C and TG concentrations are considered to be the risk factors for cardiovascular disease. (35)(36)(37) Further multiple logistic regression analysis showed that the serum VEC and Vcn concentrations were associated with the prevalence of acute preoperative complications in patients with AAD. Of note, compared with patients with refractory pain, the adjusted OR for VEC concentration in patients without refractory pain increased to 1.172.…”
Section: Discussionmentioning
confidence: 96%
“…(34) In addition, high serum HDL-C and TG concentrations are considered to be the risk factors for cardiovascular disease. (35)(36)(37) Further multiple logistic regression analysis showed that the serum VEC and Vcn concentrations were associated with the prevalence of acute preoperative complications in patients with AAD. Of note, compared with patients with refractory pain, the adjusted OR for VEC concentration in patients without refractory pain increased to 1.172.…”
Section: Discussionmentioning
confidence: 96%
“…Low HDL-cholesterol: serum HDL-cholesterol < 1.0 mmol/l (40 mg/dl) in men or < 0.9 mmol/l (50 mg/dl) in women. 5. High fasting glucose: fasting serum glucose ≥ 6.1 mmol/l (110 mg/dl).…”
Section: De Nitionsmentioning
confidence: 99%
“…In uence factors associated with TBAD include hypertension, diabetes mellitus (DM), obesity, and hyperlipidemia, which are also common components of MS. As estimated, approximately 80% of patients who develop an aortic dissection have hypertension, 31% of patients have atherosclerosis [3][4]. Nevertheless, the role of association diabetes mellitus, obesity, triglyceride and high-density lipoprotein cholesterol in TBAD remains unclear with controversial or scarce research ndings [5].…”
Section: Introductionmentioning
confidence: 99%
“…Acute aortic dissection (AAD) is a life-threatening vascular disease with a high death rate and morbidity [1,2]. An untreated AAD can lead to increased mortality of 1-2% per hour after symptom onset.…”
Section: Introductionmentioning
confidence: 99%